Bioinspired skin towards next-generation rehabilitation medicine - Wang, Zhenghui; Xiao, Chen; Roy, Mridul; Yuan, Zhiyao; Zhao, Lingyu; Liu, Yanting; Guo, Xuejun; Lu, Ping (Frontiers in Bioengineering and Biotechnology, 2023)
The rapid progress of interdisciplinary researches from materials science, biotechnologies, biomedical engineering, and medicine, have resulted in the emerging of bioinspired skins for various fantasticating applications. Bioinspired skin is highly promising in the application of rehabilitation medicine owing to their advantages, including personalization, excellent biocompatibility, multi-functionality, easy maintainability and wearability, and mass production. Therefore, this review presents the recent progress of bioinspired skin towards next-generation rehabilitation medicine. The classification is first briefly introduced. Then, various applications of bioinspired skins in the field of rehabilitation medicine at home and abroad are discussed in detail. Last, we provide the challenges we are facing now, and propose the next research directions.